A meta-analysis evaluating indirectly GLP-1 receptor agonists and arrhythmias in patients with type 2 diabetes and myocardial infarction - Liu, Zhijie; Bian, Ning; Wu, Shaorong; Fan, Yiming; Li, Hairui; Yu, Jian; Guo, Jun; Chen, Dongdong (Frontiers in Cardiovascular Medicine, 2022)
Aims: At present, the effects of Glucagon-Like Peptide 1 Receptor agonists (GLP-1RAs) on arrhythmia in patients with type 2 diabetes mellitus (T2DM) and myocardial infarction (MI) are still unclear. Hence, this systematic review and meta-analysis aimed to investigate this association. Methods and results: PubMed, Embase, Cochrane Library, and Web of Science were searched from inception to 30 April 2022. Randomized controlled trials (RCTs) meeting the proportion of patients with T2DM and MI > 30% to assess the efficacy or safety of GLP-1RAs compared to placebo were included to verify our purpose indirectly. The outcomes of interest included atrial arrhythmias, ventricular arrhythmias，atrioventricular block (AVB), sinus arrhythmia, and cardiac arrest. Relative risk (RR) and 95% confidence intervals (CI) were pooled using a random-effects model. We included five RCTs with altogether 31,314 patients. In these trials, the highest proportion of patients with T2DM and MI was 82.6%, while the lowest was 30.7%. Compared to placebo, GLP-1RAs were associated with a lower risk of atrial arrhythmias (RR 0.81, 95% CI 0.70–0.95). There was no significant difference in the risk of ventricular arrhythmias (RR 1.26, 95% CI 0.87-1.80), AVB (RR 0.95, 95% CI 0.63-1.42), sinus arrhythmia (RR 0.62, 95% CI 0.26-1.49), and cardiac arrest (RR 0.97, 95% CI 0.52-1.83) between groups. Conclusion: GLP-1RAs may be associated with reduced risk for atrial arrhythmias, which seems more significant for patients with T2DM combined with MI. More studies are needed to clarify the definitive anti-arrhythmic role of this drug.